2018
DOI: 10.1016/j.hpb.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Does blood group affect survival following pancreatoduodenectomy for periampullary malignancy?

Abstract: There is a difference in the distribution of blood groups across the different types of periampullary cancers. Survival is shorter among blood group A patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(32 reference statements)
1
1
1
Order By: Relevance
“…However, the results of this study stand in contrast to recent work by Khalil et al 12 and Rahbari et al, 14 both of whom found a significant survival advantage in patients with blood group O. Notably, Khalil et al 12 found a significant survival difference when comparing ABO blood group across all periampullary cancers, but this difference disappeared when looking exclusively at PDAC patients. Rahbari et al 14 found a significant survival difference only on multivariate, but not on univariate analysis of blood groups.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the results of this study stand in contrast to recent work by Khalil et al 12 and Rahbari et al, 14 both of whom found a significant survival advantage in patients with blood group O. Notably, Khalil et al 12 found a significant survival difference when comparing ABO blood group across all periampullary cancers, but this difference disappeared when looking exclusively at PDAC patients. Rahbari et al 14 found a significant survival difference only on multivariate, but not on univariate analysis of blood groups.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in line with previous work by Dandona et al, 17 Wang et al 15 and El Jellas et al, 16 all of whom found no survival advantage in patients with blood group O. However, the results of this study stand in contrast to recent work by Khalil et al 12 and Rahbari et al, 14 both of whom found a significant survival advantage in patients with blood group O. Notably, Khalil et al 12 found a significant survival difference when comparing ABO blood group across all periampullary cancers, but this difference disappeared when looking exclusively at PDAC patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation